"Glossed over and missing": Preservice teachers learn about slavery in Canada. (2nd October 2022) - Wright-Maley, Cory
ABSTRACT: The more than 200 years of chattel slavery in Canada is an example of the country's occluded history predicated on structural racism. This study of preservice elementary teachers in a social studies methods course helps to reveal how the history of Black enslavement in Canada has been effectively erased from the national consciousness. Using a symbolic interactionism/grounded theory methodology, I seek to make meaning from more than 70 preservice teachers' written responses to a reading on slavery and abolition in Canada. This study's findings help reveal some of the challenges to, and possibilities for, interrogating historical consciousness and national identity narratives as a process of learning within the contexts of methods courses.